Identification of salmonella spp, listeria monocytogenes, and indicator microorganisms in commercialized raw meats and fresh sausages from Uruguaiana, Rio Grande do Sul, Brazil - Soares, Vanessa Mendonça; Padilha, Matheus Beltrame; De Guerra, Maria Eduarda Moraes; Schneider, Fernando Alves; Gasparetto, Raíssa; Dos Santos, Emanoelli Aparecida Rodrigues; Tadielo, Leonardo Ereno [UNESP]; Brum, Mário Celso Sperotto; Traesel, Carolina Kist; Pereira, Juliano Gonçalves [UNESP] (FapUNIFESP (SciELO), 2021)
This study evaluated the sanitary hygienic quality and the presence of pathogenic microorganisms in raw meats and fresh sausages marketed in the city of Uruguaiana, Rio Grande do Sul (RS), Brazil. We analyzed 238 samples of fresh sausages, beef, pork, and chicken from 18 commercial establishments (butchers, supermarkets, and groceries). Samples were subjected to enumerate hygiene indicator microorganisms (mesophilic aerobes and enterobacteria) and detection of Salmonella spp and Listeria monocytogenes. The mean counts of mesophilic aerobes and enterobacteria were 5.09 and 3.54 log CFU/g, respectively. Beef samples presented the highest frequency of Salmonella spp (7.93%) and fresh sausages present the highest frequency of L. monocytogenes (19.04%). Among the analyzed samples, 43.70% did not comply with the microbiological parameters established by the Brazilian Ministry of Health. The presence of Salmonella spp and L. monocytogenes in different samples and commercial establishments demonstrate the failures of good manufacturing practices in industrial environmental and retails points and the need to train food handlers to reduce the exposure of consumers to potential risks.
Identificação de Salmonella spp, Listeria monocytogenes e micro-organismos indicadores em carnes cruas e embutidos frescais comercializados na cidade de Uruguaiana, Rio Grande do Sul, Brasil
Keywords: Microbial contamination; Pathogens; Retail trade; Sanitary hygienic quality